The Effect of Variation of Amperes and Water Backing Technique on Microstructure, Mechanical Properties, and Dimensional of Welding Process on Crosshead Valve With GTAW Method - Rahmat Ashari; Aji Ridhotullah; Sulistijono Sulistijono; Rocky Andiana; Yoel Rizky (Institut Teknologi Sepuluh Nopember, 2018)
In this study, evolution of microstructural, hardness value, and dimensional crosshead valve that has been welded with Ni-Cr-B-Si-C alloys deposit are investigated. Ni-Cr-B-Si-C alloys has deposited to replace nickel alloys on component that have wear. The process that used is GTAW welding process with variation of amperes and with or without using water backing technique. Result from this study, on weld metal microstructure with variation of heat input and water backing method made same structure like original materials. On base metal microstructure, resulting same structrue as original material that consist of ferrite and pearlite. However, on HAZ which used 140 A on welding current and water backing method produced martensite structure. The greater heat input make a greater hardness value on weld metal and water backing can keep the original hardness from material. In addition, heat input and water backing that used in this processs not cause a deformation on crosshead components result from dimensional test which still suitable with original component specification.